Using Short Story To Improve Students’ Reading Skill At VIII Grade Of SMP Negeri 1 Pulau-Pulau Babar - Etwiory, Rosanthy; Lekawael, Rosina F. J.; Meyer, Fredi (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2022)
Short stories can be effectively used in classroom reading activities, as demonstrated by a Classroom Action Research study conducted at SMP Negeri 1 Pulau-Pulau Babar. This study aimed to determine how short stories improve reading skills among eighth-grade students and to gauge their responses to this method. The research involved two cycles, each comprising four meetings that included planning, action, observing, and reflecting. Data was collected through tests, questionnaires, and observations, with the involvement of an English teacher from the school. The results indicated that incorporating short stories significantly enhanced students' reading skills, as evidenced by their increased engagement and enthusiasm. In Cycle I, 60% of students met the minimum competency standard (KKM), and this figure rose to 90% in Cycle II.